2019
DOI: 10.3390/bs9090092
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Multilingualism and Cognitive Abilities: Preliminary Data on the Contribution of Language Proficiency and Use in Different Modalities

Abstract: This exploratory study focuses on sequential bi-/multilinguals (specifically, nonimmigrant young Dutch native speakers who learned at least one foreign language (FL) at or after the age of 5) and investigates the impact of proficiency-based and amount-of-use-based degrees of multilingualism in different modalities (i.e., speaking, listening, writing, reading) on inhibition, disengagement of attention, and switching. Fifty-four participants completed a comprehensive background questionnaire, a nonverbal fluid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 89 publications
2
12
0
Order By: Relevance
“…So far, small study samples have been often used in research on the bilingual advantage in cognitive control and, to a lesser degree, in research on bilingualism and the cognitive reserve hypothesis. Furthermore, whether the bilingual advantage in cognitive control and the contribution to cognitive reserve are mainly limited to extremely proficient bilinguals that use both languages at a professional level the whole day, like interpreters, [25] and to multilingual individuals who have to switch and suppress languages extensively to a larger extent than bilinguals should be explicitly investigated [34]. Last, but not least, the use of longitudinal designs is highly recommended because L2 learning is a complex, dynamic process [15].…”
Section: Discussionmentioning
confidence: 99%
“…So far, small study samples have been often used in research on the bilingual advantage in cognitive control and, to a lesser degree, in research on bilingualism and the cognitive reserve hypothesis. Furthermore, whether the bilingual advantage in cognitive control and the contribution to cognitive reserve are mainly limited to extremely proficient bilinguals that use both languages at a professional level the whole day, like interpreters, [25] and to multilingual individuals who have to switch and suppress languages extensively to a larger extent than bilinguals should be explicitly investigated [34]. Last, but not least, the use of longitudinal designs is highly recommended because L2 learning is a complex, dynamic process [15].…”
Section: Discussionmentioning
confidence: 99%
“…So far, small study samples have been often used in research on the bilingual advantage in cognitive control and, to a lesser degree, in research on bilingualism and the cognitive reserve hypothesis. Furthermore, whether the bilingual advantage in cognitive control and the contribution to cognitive reserve are mainly limited to extremely proficient bilinguals that use both languages at a professional level the whole day, like interpreters, [25] and to multilingual individuals who have to switch and suppress languages extensively to a larger extent than bilinguals should be explicitly investigated [34]. Last, but not least, the use of longitudinal designs is highly recommended because L2 learning is a complex, dynamic process [15].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of proficiency-based and amount-of-use-based degrees of multilingualism in different modalities (i.e., speaking, listening, writing, and reading) on inhibition, disengagement of attention, and switching were investigated in 54 late bi-/multilinguals. Their results [34] showed that only proficiency-based degrees of multilingualism affected cognitive abilities. In particular, a marginally significant independent positive effect of mean proficiency in foreign languages in the writing and the listening modalities on inhibition (in the literature known as a flanker effect [29]) was found, as was a significant negative effect of L2 proficiency in the listening modality on disengagement of attention (in the literature referred to as a sequential congruency effect [35]).…”
Section: Bilingual Advantage In Cognitive Controlmentioning
confidence: 98%
See 2 more Smart Citations